(untitled) (Research, Society and Development, 2020)
This research aims to verify the relationship between organizational support and organizational social capital in workers. With the social and economic events in the last ten years, companies have sought to assess the intrinsic aspects of workers in terms of productivity and creativity. Thus, management processes of incentive policies and more interpersonal organizational practices are receiving more investments. 401 workers from the State of Rio Grande do Norte participated in the study, most of them were between 30 and 44 years old, were men, work in the public sector and have an income above 4,001.00. They responded to the Perception Scale of Organizational Support, Organizational Social Capital and socio-demographic data, electronically through Google forms. In the AMOS 21.0 statistical program, the intended analysis was carried out, confirming the hypothesis that organizational support positively influences social capital It is noteworthy that, considering these results, how much organizational support can influence the quality of production and social interaction in the work environment, when focused on social capital.